2006
DOI: 10.1007/s11249-006-9075-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tribochemical reactions of antiwear additives on heterogeneous surface layers in boundary lubrication

Abstract: The article discusses methods for the deposition of antiwear, composite coatings with a metallic matrix. The Ni-P-Al 2 O 3 composite layers were superimposed on carbon steel elements using the electroless plating technique. A comparative analysis of adsorptive interactions was carried out for model systems with antiwear characteristics, i.e., for the Ni-P matrix, and the composite material containing micro-dispersive corundum, i.e., Ni-P-Al 2 O 3 . The paper presents the results of tribological tests and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Various systems have been developed so far of exceptional in some cases properties. Indicative systems with reinforcing phases, such as Al 2 O 3 [19][20][21][22][23], SiO 2 [24], Cr 2 O 3 [25], ZnO [26], SiC [27][28][29], B 4 C [30], WC [31], CNTs [32,33], Graphite [34], BN [35], Diamond [21,33], Si3N4 [27,36], CeO 2 [37], MoS 2 [38,39], PTFE [40,41], and combinations of them [42,43] are reported.…”
Section: Introductionmentioning
confidence: 99%
“…Various systems have been developed so far of exceptional in some cases properties. Indicative systems with reinforcing phases, such as Al 2 O 3 [19][20][21][22][23], SiO 2 [24], Cr 2 O 3 [25], ZnO [26], SiC [27][28][29], B 4 C [30], WC [31], CNTs [32,33], Graphite [34], BN [35], Diamond [21,33], Si3N4 [27,36], CeO 2 [37], MoS 2 [38,39], PTFE [40,41], and combinations of them [42,43] are reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was also reported that WC/C coatings exhibit excellent behaviour under heavily loaded conditions of sliding and rolling contact (Krantz et al, 2003). Many efforts have been made in recent years to understand the lubrication of coated components (Michalczewski et al, 2009;Vlad et al, 2010;Podgornik et al, 2005;Madej et al, 2006;Kula et al, 1997). Despite many papers concerning this topic, the wear mechanism under scuffing conditions of coated parts is far from a complete explanation.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of a lubricant additive is measured by adsorption, hence the frequent application of zinc dialkyldithiophosphate, ZDTP. The addition of this substance causes that the coating resistance to wear, corrosion, and antioxidants is higher [7,8]. The behavior of ZDTP in a friction joint is very complex and depends on numerous factors, for instance, the type and properties of friction surfaces, load, and temperature [9].…”
Section: Introductionmentioning
confidence: 99%